Toxoplasma gondii-Induced Long-Term Changes in the Upper Intestinal Microflora during the Chronic Stage of Infection - Emese Prandovszky; Ye Li; Sarven Sabunciyan; Curtis B. Steinfeldt; Lauro Nathaniel Avalos; Kristin L. Gressitt; James R. White; Emily G. Severance; Mikhail V. Pletnikov; Jianchun Xiao; Robert H. Yolken (Scientifica)
Toxoplasma gondii is an obligate intracellular parasite with worldwide distribution. Felines are the definitive hosts supporting the complete life cycle of T. gondii. However, other warm-blooded animals such as rodents and humans can also be infected. Infection of such secondary hosts results in long-term infection characterized by the presence of tissue cysts in the brain and other organs. While it is known that T. gondii infection in rodents is associated with behavioral changes, the mechanisms behind these changes remain unclear. Alterations of the host intestinal microflora are recognized as a prominent role player in shaping host behavior and cognition. It has been shown that acute T. gondii infection of mice results in microflora changes as a result of gastrointestinal inflammation in inbred mouse models. The long-term effects of chronic T. gondii infection on microbial communities, however, are unknown. In this study, after we verified using our model in terms of measuring microflora changes during an acute episode of toxoplasmosis, we assessed the microbiome changes that occur during a long-term infection; then we further investigated these changes in a follow-up study of chronic infection. These analyses were performed by constructing and sequencing 16S rRNA amplicon DNA libraries from small intestine fecal specimens. We found that acute infection with the GT1 strain of T. gondii caused an enrichment of Bacteroidetes compared with controls in CD1 mice. Strikingly, this enrichment upheld throughout long-term chronic infection. The potential biological consequences of this alteration in rodents and humans should be subjected to further exploration.